2008
DOI: 10.3892/ijo.32.2.333
|View full text |Cite
|
Sign up to set email alerts
|

Expression of p16INK4a and MIB-1 in relation to histopathology and HPV types in cervical adenocarcinoma

Abstract: A total of 101 primary cervical adenocarcinomas were analyzed for the presence of p16 INK4a and MIB-1 expression in correlation with the presence of 'high-risk' types of human papillomavirus (HR-HPV) and clinical outcome.We found that adenocarcinoma grading showed a significant negative correlation to p16 INK4a levels (p=0.001): i.e. we found less intense p16 staining in poorly differentiated tumors than in more highly differentiated tumors as well as a highly significant correlation between HPV infection and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 38 publications
(49 reference statements)
2
21
0
Order By: Relevance
“…17,21,43,44 However, in cervical and vulvar carcinoma, there are conflicting data on the prognostic value of these proliferation markers. In cervical adenocarcinoma, high levels of Ki67 staining was associated with more advanced stage at diagnosis and low grade, 45 whereas no prognostic value of Ki67 was demonstrated in a study on squamous cell carcinoma of the cervix. 46 However, cyclin A was found to be a poor prognostic indicator for squamous cell carcinoma of the cervix.…”
Section: Cyclin a And Ki67mentioning
confidence: 86%
“…17,21,43,44 However, in cervical and vulvar carcinoma, there are conflicting data on the prognostic value of these proliferation markers. In cervical adenocarcinoma, high levels of Ki67 staining was associated with more advanced stage at diagnosis and low grade, 45 whereas no prognostic value of Ki67 was demonstrated in a study on squamous cell carcinoma of the cervix. 46 However, cyclin A was found to be a poor prognostic indicator for squamous cell carcinoma of the cervix.…”
Section: Cyclin a And Ki67mentioning
confidence: 86%
“…There was data on the positive expressions of 1 or more of 17 biomarkers in endometrioid adenocarcinoma cases versus the 5 comparators 1517, 22, 23, 25, 26, 28, 29, 30, 31, 33–35, 3739, 40, 42–44, 47–49, 5255, 62, 63 . A total of 5 biomarkers (ubiquitin, telomerase, CTK20, CTK7, and EMA) were compared once and only in comparison to mucinous adenocarcinoma.…”
Section: Resultsmentioning
confidence: 99%
“…There was data on the positive expression of 1 or more of 11 biomarkers in adenosquamous carcinoma cases versus the 5 comparators 15, 16, 22, 25, 28, 29, 38, 39, 40, 43, 44, 47, 48, 52, 53, 55, 62, 63 . PTEN and VILI1 were compared once and only in comparison to mucinous adenocarcinoma.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous study of cervical adenocarcinoma, we showed that levels of the tumor suppressor protein p16INK4a are higher in poorly differentiated tumors and in HPV-positive tumors than in HPV-negative tumors (16). No correlation was found between clinical outcome, stage, and histological grade in this study of patients with detectable full-length E6/E7 mRNA.…”
Section: ------------------------------------------------------------mentioning
confidence: 86%
“…The study includes formaldehyde-fixed paraffin-embedded tumor tissue specimens from 98 primary cervical adenocarcinomas diagnosed and surgically treated at Karolinska University Hospital-Huddinge between 1992 and 2000. Clinical information from these cases has in part been previously published (16).…”
Section: Methodsmentioning
confidence: 99%